Volcanic risk and tourism in southern Iceland:implications for hazard, risk and emergency response education and training - Bird, Deanne K.; Gisladottir, Gudrun; Dominey-Howes, Dale (Journal of Volcanology and Geothermal Research, 2010)
This paper examines the relationship between volcanic risk and the tourism sector in southern Iceland and the complex challenge emergency management officials face in developing effective volcanic risk mitigation strategies. An early warning system and emergency response procedures were developed for communities surrounding Katla, the volcano underlying the Mýrdalsjökull ice cap. However, prior to and during the 2007 tourist season these mitigation efforts were not effectively communicated to stakeholders located in the tourist destination of Thornórsmörk despite its location within the hazard zone of Katla. The hazard zone represents the potential extent of a catastrophic jökulhlaup (glacial outburst flood). Furthermore, volcanic risk mitigation efforts in Thornórsmörk were based solely on information derived from physical investigations of volcanic hazards. They did not consider the human dimension of risk. In order to address this gap and provide support to current risk mitigation efforts, questionnaire surveys were used to investigate tourists' and tourism employees' hazard knowledge, risk perception, adoption of personal preparedness measures, predicted behaviour if faced with a Katla eruption and views on education. Results indicate that tourists lack hazard knowledge and they do not adopt preparedness measures to deal with the consequences of an eruption. Despite a high level of risk perception, tourism employees lack knowledge about the early warning system and emergency response procedures. Results show that tourists are positive about receiving information concerning Katla and its hazards and therefore, the reticence of tourism employees with respect to disseminating hazard information is unjustified. In order to improve the tourism sector's collective capacity to positively respond during a future eruption, recommendations are made to ensure adequate dissemination of hazard, risk and emergency response information. Most importantly education campaigns should focus on: (a) increasing tourists' ...